Clinical Process in Blockchain for Patient Security in Home Care - Mendes, David; Galvão, Hugo; Eiras, Margarida; Lopes, Manuel (Journal of the Institute of Engineering, 2018)
We explain how a solution for data privacy, and specifically for cognitive security, can be enforced and guaranteed using blockchain technology in SAAL (Smart Ambient Assisted Living) environments. Using our proposal the access to a patient’s clinical process is secure for the adequate interested and authorized parties while resist tampering and ransomware attacks that have recently plagued the HIS (Hospital Information Systems) in various countries. Journal of the Institute of Engineering, 2017, 13(1): 37-47